Business Games for Leadership Development: A Systematic Review. (August 2013) - Lopes, Mauricio Capobianco; Fialho, Francisco A. P.; Cunha, Cristiano J. C. A.; Niveiros, Sofia Inés
Leadership development poses great challenges to modern organizations. One possible method to develop leaders is the use of experiential techniques based on business games. The objective of this article was to identify, based on literature, business games used in leadership development and to examine how they contribute to the qualification of the leaders. In particular, the article analyzes business games in which elements of leadership development were present as part of the computer model (simulator). The article describes the goals of the games, their pedagogical and technical features, their relation to leadership theories, and their effectiveness in leadership development. The methodology used was systematic review conducted in SCOPUS, ISI, and BKL (Bernie Keys Library) databases. The review identified five games that met the criteria and objectives of this research. This study shows that using business games for leadership development is still a hard task. It points up some problems and difficulties in this task and suggests ways to develop more effective methods for leadership development with business games.